Designing Instructional Materials for First Semester English Learners from Basic to Intermediate Proficiency Based on Need Analysis - Alda Alda; Sam Hermansyah; Andi Sadapotto; Jamaluddin Ahmad; Buhari Buhari; Nuraini Kasman (Universitas Muhammadiyah Enrekang, 2025)
In an increasingly globalized world, English proficiency is essential for academic and professional success. However, many first-semester English Education students at Universitas Muhammadiyah Sidenreng Rappang remain at a basic proficiency level, which hinders their progression toward intermediate competence as required by the Common European Framework of Reference for Languages (CEFR). This research addresses the lack of tailored instructional materials that support students’ transition from basic to intermediate proficiency. This study aims to design and develop instructional materials based on a comprehensive needs analysis. Employing a Research and Development (R&D) methodology with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the research engaged 30 first-semester students, three lecturers, and five alumni. Data were collected through questionnaires, interviews, diagnostic tests, pretests, posttests, and classroom observations. Quantitative data were analyzed using descriptive statistics and paired sample t-tests, while qualitative data were examined thematically. The findings revealed that students faced significant challenges in speaking fluently, comprehending oral input at natural speed, identifying main ideas in reading, and organizing ideas in writing. The developed instructional materials, which integrated task-based and skill-based approaches aligned with CEFR descriptors, demonstrated effectiveness in bridging these gaps. Posttest results showed significant improvement across all four language skills, confirming the materials’ role in supporting students’ transition toward intermediate proficiency. This research contributes to English language education by providing empirically validated instructional materials that respond to learners’ actual needs. It offers practical implications for lecturers, institutions, and future researchers in designing relevant and level-appropriate English learning resources.